Molybdenum sulfide for energy applications - Chua, Xing Juan (2017)
This thesis examines the use of molybdenum sulfide materials for energy related applications, specifically into electrocatalysis for hydrogen evolution reaction (HER). It looked into some of the fundamental aspects of the practical application of molybdenum sulfide material when used as a starting material or for the electroanalysis measurements. The thesis first explores the variations in the electrocatalytic performances of molybdenum disulfide from various commercial sources and then investigates into the use of various solvents as dispersion medium for molybdenum sulfide materials. Extensive characterisation tools were employed and is discussed with respect to the varying electrocatalytic efficiencies of molybdenum disulfide materials obtained from the various sources. Contrary to conventional research direction which looks into the efficiency of solvent in the exfoliation of bulk molybdenum disulfide, the fundamental aspects concerning the practice of electroanalysis measurements were looked into. The drop-casting method is commonly employed with solid materials suspended in a known solvent. However, much less is known with respect to the effect of these solvents on the electrocatalysis performances. Thus, the second part of this thesis seeks to examine and discuss these variations.